2019
DOI: 10.1016/j.energy.2019.05.097
|View full text |Cite
|
Sign up to set email alerts
|

Correlating photovoltaic soiling losses to waveband and single-value transmittance measurements

Abstract: This paper presents the results of an investigation on the spectral losses of photovoltaic (PV) soiling. The transmittance of a glass coupon exposed to natural soiling outdoors in Jaén, southern Spain, has been measured weekly and used to estimate the soiling losses that various types of photovoltaic materials would experience if installed in the same location. The results suggest that measuring the hemispherical transmittance of the soiling accumulated on a PV glass coupon can give enough information to quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…Optical sensors take a single measurement and thus neglect the wavelength dependent effects of soiling, together with the different spectral responses possible for the various types of PV absorber materials. In reality, the transmission of light due to soiling has a gradually increasing spectral profile [3,4], with larger losses in the blue region, as is shown in Fig. 1.…”
Section: Background and Motivationmentioning
confidence: 94%
See 4 more Smart Citations
“…Optical sensors take a single measurement and thus neglect the wavelength dependent effects of soiling, together with the different spectral responses possible for the various types of PV absorber materials. In reality, the transmission of light due to soiling has a gradually increasing spectral profile [3,4], with larger losses in the blue region, as is shown in Fig. 1.…”
Section: Background and Motivationmentioning
confidence: 94%
“…1. In our previous study [3], we demonstrated that a transmittance measurement at a single wavelength or the use of an average transmittance can be successfully used to identify the soiling profile trends over time, with extreme accuracy (R 2 >0.99). Each PV absorber material (PV technology) had a preferred wavelength at which the measurement returned the lowest error.…”
Section: Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations